Dynamic analysis of Tapping Panel Dryness in Hevea brasiliensis reveals new insights on this physiological syndrome affecting latex production. Issue 10 (October 2022) - Herlinawati, Eva; Montoro, Pascal; Ismawanto, Sigit; Syafaah, Afdholiatus; Aji, Martini; Giner, Michel; Flori, Albert; Gohet, Eric; Oktavia, Fetrina
Abstract: Tapping Panel Dryness (TPD) is a physiological disorder affecting natural rubber production in Hevea brasiliensis . TPD is associated with clonal susceptibility and overexploitation of rubber trees. Most studies are based on a binary point view of the absence or presence of TPD. This study sets out to characterize the dynamic of the TPD onset through the monthly monitoring of the dry cut length. This reveals the presence of dry spots on the tapped panel of any trees. The frequency of these dry spots increases dramatically in trees developing high level of TPD. Brown bast is an irreversible form of TPD. Brown bast is correlated to a high level of dry cut length. Application of an intensive harvesting system induces early TPD occurrence, which facilitates the study of TPD. Among latex diagnosis parameters, only sucrose content is significantly associated with TPD. Other parameters are more prone to environmental effects and are not reliable as physiological markers. These findings explain the contradictory conclusions of some papers. This study suggests to use intensive harvesting system and monitor the dry cut length for genetic analysis of TPD. Abstract : Dry cut; Marker; Phenotyping; Rubber; Sucrose; Yield.